Four Needles in a Haystack: A Systematic Review Assessing Quality of Health Care in Specialty Practice by Practice Type - Ellis, Shellie D.; Karim, Saleema A.; Vukas, Rachel R.; Marx, Daniel; Uddin, Jalal (Inquiry (Chicago), 2018)
Specialists, who represent 60% of physicians in the United States, are consolidating into large group practices, but the degree to which group practice type facilitates the delivery of high quality of care in specialty settings is unknown. We conducted a systematic literature review to identify the impact of group practice type on the quality of care among specialty providers. The search resulted in 913 articles, of which only 4 met inclusion criteria. Studies were of moderate methodological quality. From the limited evidence available, we hypothesize that solo specialists deliver care that is inferior to their peers in group practice, whether measured by patient satisfaction ratings or adherence to guideline-based care. However, solo specialists and multidisciplinary group specialists may be more likely to provide some specialized services compared with their single-specialty group peers. Insufficient research compares quality of care among different practice types in specialty care. Substantial opportunity exists to test the degree to which organizational factors, whether size of practice or the mix of providers within the practice, influence quality of care in specialty settings.